Cases of (w) and (y) letter as the first radical of roots: weakening (ilāl) as phonetic phenomena in Al-Shafia book by Ibn Al-hajeb (modern phonetic study) - Ali Al-Ta'ee, Hasan Hameed Mohsin (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at treating of this phenomenon Causation occurs for semi transactions in linguistic structures ,its address (the conditions of the waw and yaa, they are faan) , through what Ibn Al-Hajib covered in his book Al-Shafi’a, as he devotes a special topic to them. This research has relied on its study and treatment of this causal issue on the data of the modern audio lesson and its requirements, because the morphological level is not taught in isolation from other levels of the linguistic lesson, as it is closely related to the phonemic lesson .The study has draft a set of vocal laws to use to solve the problems of outstanding morphological problems, they are: (the laws of similarity andthe difference).Likewise, to seek the help of the Arabic phoneme, its importance is assuming that the structural fabric reaches the structure, the purpose of all of that is to review modern audio treatmentsthis phenomenon, compared with the treatment of the ancients of the phenomenon itself, and to determine the extent of compatibility and discrepancies in the approach when presenting similar causes.